Oxidative Stress Markers in Chronic Kidney Disease with Emphasis on Diabetic Nephropathy - Nina Vodošek Hojs; Sebastjan Bevc; Robert Ekart; Radovan Hojs (MDPI AG, 2020)
Diabetes prevalence is increasing worldwide, especially through the increase of type 2 diabetes. Diabetic nephropathy occurs in up to 40% of diabetic patients and is the leading cause of end-stage renal disease. Various factors affect the development and progression of diabetic nephropathy. Hyperglycaemia increases free radical production, resulting in oxidative stress, which plays an important role in the pathogenesis of diabetic nephropathy. Free radicals have a short half-life and are difficult to measure. In contrast, oxidation products, including lipid peroxidation, protein oxidation, and nucleic acid oxidation, have longer lifetimes and are used to evaluate oxidative stress. In recent years, different oxidative stress biomarkers associated with diabetic nephropathy have been found. This review summarises current evidence of oxidative stress biomarkers in patients with diabetic nephropathy. Although some of them are promising, they cannot replace currently used clinical biomarkers (eGFR, proteinuria) in the development and progression of diabetic nephropathy.